A study of the factors behind the maternal and infantile mortality of black American woman - Antender, Sydney (Revista Avesso: Pensamento, Memória e Sociedade, 2020)
This paper delves into the factors that contribute to the racial disparity of maternal and infantile mortality rate in the United States. According to a study done by the Center for Disease control, black women in the United States are overall two to three times more likely to die than white women. This paper asks the question “what is causing this disparity and what are the consequences and factors to this increased maternal mortality rate for African American women". This paper uncovers that from the beginning of the creation of allopathic healthcare in the late 1800’s black birthing has become more dangerous for mothers and children. Throughout case studies and interviews, black women feel less respected by health care professionals and are less likely to be listened to. There is also evidence that racial stress of living in an overwhelming racialized white country has decreased the health outlooks for both mother and newborns born in the U.S.